Correction of Eyes and Lip Canting after Bimaxillary Orthognathic Surgery - Yang, Chae-Eun; Bae, Jae Young; Lee, Jina; Lew, Dae Hyun (Yonsei medical journal, 2018)
Patients who have a lower facial asymmetry with compensatory head posture (developmental facial asymmetry) may have minor temporomandibular (T-M) joint problems and tend to mask their asymmetry by tilting the head for camouflage of their chin deviation. However, this compensatory head posture can give the impression of orbital dystopia and c spine deviation. When these patients undergo bimaxillary orthognathic surgery, orbital canting and head tilting improves gradually without the need for camouflage, and bleary eyes become clearer. We evaluated 13 patients who underwent LeFort I osteotomy combined with bilateral sagittal split osteotomy of the mandible for developmental facial asymmetry to quantitatively observe whole facial postural changes after surgery. Pre-operative and post-operative 1:1 full-face photographs of the patients were analyzed to compare the degrees of head tilting and orbital canting and the sizes of the eye opening. After bimaxillary orthognathic surgery, eye canting decreased from 2.6° to 1.5°, eye and lip lines came closer to parallel, and the degree of head tilting decreased from 3.4° to 1.3°. The eyes also appeared to open wider. Correction of lower facial skeletal asymmetry through bimaxillary orthognathic surgery improved head tilting and orbital canting gradually by eliminating the need of compensatory head posture. Facial expressions also changed as the size of the eyes increased due to the reduction of facial muscle tension caused by T-M joint dysfunction.